Bio-chemical characterization of rhizobia isolated from root nodules of Velvet bean (Mucuna pruriens L.) (Our Nature, 2017)
Rhizobia are the symbiotic bacteria found in the soil which have potential ability to convert atmospheric di-nitrogen into usable form. A total of ten rhizobial strains were isolated from the root nodules of a medicinal legume Mucuna pruriens (L.) that commonly grow in the foothills of the Himalaya. All the ten   strains isolated from different locations of same area were morphologically, biochemically and physiologically characterized based on the Bergey’s Manual of systematic Bacteriology. They were tested for the antibiotics sensitivity. The isolates showed high sensitivity to amoxicillin and least to erythromycin. Authentication test was done in eleven legumes but shown nodulations only in Trigonella foenum-graecum, Mucuna pruriens and Medicago sativa. The morphology, physiology, biochemical and infection test studies carried out justifies that the bacteria isolated belonged to the species of Rhizobium meliloti.